Requirements of knowledge sharing for group decision support system - Mohamed Dahlan, Halina (IEEE, 2011)
Group decision support systems (GDSS) have evolved from applications designed primarily to support decision making for groups. Indeed, it is generally accepted that improvements of group support systems is a longstanding interest to organizational researchers, containing solid practical as well as scientific significance. Within this practice, there is increasing challenge to improve the exchange of knowledge among group members in order to enhance GDSS capability of knowledge sharing. Therefore, the paper investigates the current GDSS situation and analyzing the requirements of knowledge sharing (KS) to enhance GDSS. It is hoped that these findings will aid to provide GDSS systems with the solid capability of knowledge sharing.